Pengaruh Penggunaan Model Pembelajaran Picture And Picture Terhadap Hasil Belajar Pendidikan Agama Islam Di SMP Qur’an Al-Zamriyah Islamic Boarding School Kecamatan Payakumbuh - Jamilatunnisa Jamilatunnisa; Arifmiboy Arifmiboy; Iswantir M; Charles Charles (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the importance of creativity in learning, especially in the context of using Picture and Picture Cooperative Learning Model in Islamic Religious Education subject in a secondary school. The article emphasizes that creative learning models can improve learners' learning outcomes, especially when compared to more traditional learning models such as the Direct Learning Model. The research method used was experimental with a Quasi Experiment design, where two classes were selected as samples: one class applied the Picture and Picture Cooperative Learning Model as the experimental class, while the other class applied the traditional learning model. Data was collected through pre- and post-learning tests, as well as through observation of students' activeness. The results showed that the Picture and Picture Cooperative Learning Model has a significant effect on students' learning outcomes, especially in the context of learning Islamic Religious Education. This model allows students to be more active and creative in learning, so that their learning outcomes can be significantly improved. This research makes an important contribution to our understanding of the importance of creativity in learning and its relevance to learners' learning outcomes. Translated with www.DeepL.com/Translator (free version)